CCR8 Signaling via CCL1 Regulates Responses of Intestinal IFN-γ Producing Innate Lymphoid CelIs and Protects From Experimental Colitis - Kang, Le; Schmalzl, Angelika; Leupold, Tamara; Gonzalez-Acera, Miguel; Atreya, Raja; Neurath, Markus; Becker, Christoph; Wirtz, Stefan (Frontiers in Immunology, 2021)
A diverse spectrum of immune cells populates the intestinal mucosa reflecting the continuous stimulation by luminal antigens. In lesions of patients with inflammatory bowel disease, an aberrant inflammatory process is characterized by a very prominent infiltrate of activated immune cells producing cytokines and chemokines. These mediators perpetuate intestinal inflammation or may contribute to mucosal protection depending on the cellular context. In order to further characterize this complex immune cell network in intestinal inflammation, we investigated the contribution of the chemokine receptor CCR8 to development of colitis using a mouse model of experimental inflammation. We found that CCR8−/− mice compared to wildtype controls developed strong weight loss accompanied by increased histological and endoscopic signs of mucosal damage. Further experiments revealed that this gut protective function of CCR8 seems to be selectively mediated by the chemotactic ligand CCL1, which was particularly produced by intestinal macrophages during colitis. Moreover, we newly identified CCR8 expression on a subgroup of intestinal innate lymphoid cells producing IFN-γ and linked a functional CCL1/CCR8 axis with their abundance in the gut. Our data therefore suggest that this pathway supports tissue-specific ILC functions important for intestinal homeostasis. Modulation of this regulatory circuit may represent a new strategy to treat inflammatory bowel disease in humans.
CRIS-Team Scopus Importer:2021-03-05
Keywords: CCR8; chemokines; cytokines; inflammatory bowel disease; innate immunity; innate lymphoid cell

SCAMP3 is regulated by miR-128-3p and promotes the metastasis of hepatocellular carcinoma cells through EGFR-MAPK p38 signaling pathway - Kang, Le; Zhang, Zehua; Zhao, Ying (American Journal of Translational Research, 2021)
Purpose: To explore the regulatory mechanism of secretory carrier membrane protein 3 (SCAMP3) and miR-128-3p in hepatocellular carcinoma (HCC). Patients and methods: Cancer tissues and adjacent tissues of 52 HCC patients treated in our hospital were collected to explore the prognostic factors affecting their 3-year survival. HCC cells were purchased, the gene expression of Huh-7 and MHCC97 were adjusted by transfection, and the levels of SCAMP3, miR-128-3p, EGFR, p-EGFR, MAPK p38, p-MAPK p38, N-cadherin, vimentin, E-cadherin, cell proliferation, migration, invasion, apoptosis and epithelial-mesenchymal transition (EMT) were detected. A nude mouse model of HCC was constructed to verify the effects of transfection of mimics. Results: SCAMP3 was elevated in HCC patients and cancer tissues of HCC patients, while miR-128-3p showed opposite effects. High level SCAMP3 and low level miR-128-3p were related to poor prognosis of HCC. Both of them were correlated with excessive drinking history, N-stage, M-stage and pathological differentiation degree of HCC patients, as well as prognostic factors of HCC patients. SCAMP3 up-regulation or miR-128-3p down-regulation could promote HCC cell proliferation, migration, invasion, and transcription and protein levels of EGFR, p-EGFR, MAPK p38, p-MAPK p38, N-cadherin and vimentin, and inhibit HCC cell apoptosis and transcription and protein levels of E-cadherin. Dual luciferase reporter identified the targeting relationship between SCAMP3 and miR-128-3p. When both SCAMP3 and miR-128-3p were elevated or reduced, the biological manifestation of cells was not different from that of miR-NC transfected with unrelated sequences. Besides, miR-128-3p inhibited tumor growth in the HCC model in nude mice. Conclusion: SCAMP3 can be controlled by miR-128-3p and can mediate the EGFR-MAPK p38 signaling pathway to inhibit HCC cell metastasis, which is expected to become a promising therapeutic target for HCC.
CRIS-Team Scopus Importer:2021-01-22
Keywords: EGFR-MAPK p38; Hepatocellular carcinoma; Metastasis; MiR-128-3p; SCAMP3